Cooperative game based bandwidth allocation mechanism live migration of multiple virtual machines - Yong CUI; Yu-song LIN; Run-zhi LI; Zong-min WANG (Tongxin xuebao)
In IaaS cloud computing platform, live migration of virtual machines plays a significant role in resource dy-namic dispatching and management. Under many scenarios, multiple virtual machines in the same server need to be moved online concurrently.Since live migration algorithm utilizes bandwidth as more as possible to send data, there is a bandwidth competition among the concurrent migration processes, which cannot guarantee the optimal allocation for the bandwidth and finally degrades the overall performance of the parallel live migration. A cooperative game based band-width allocation mechanism in live migration of multip virtual machines was proposed, which models the bandwidth allocation problem as a Nash bargaining game and attains a desirable bandwidth sharing scheme that guarantees Pareto optimality. Experiment results show that the proposed method can assign the bandwidth fairly and efficiently and im-prove the performance of the parallel live migration.